2007
DOI: 10.1038/sj.jhh.1002150
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the burden of arterial hypertension: what can be expected from an improved access to health care? Results from a study in 2420 unemployed subjects in the Caribbean

Abstract: -Terre, GuadeloupeHigh prevalence and poor control of hypertension have been observed in populations with low-socioeconomic status. Comparing an unemployed population with another employed population sharing the same culture, and another employed population living in another environment might enlighten the effects of factors accessible to primary prevention on the one hand and access to health care on the other hand. The objectives are, first, to describe blood pressure (BP) prevalence and control in an unempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Undoubtedly, such a high divorce rate of 78.7% and 44.9% unemployment rate among the participants in this study can trigger unhealthy social habits like smoking, drinking and drug abuse. Subscribing to this notion, Pharr et al (2012) posit that unemployment is associated with unhealthy behaviours; and study conducted by Atallah et al (2007) in the Caribbean, indicate that the high prevalence and poor control of hypertension have been observed in populations with low-socioeconomic status including poor therapeutic control in lower social classes.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, such a high divorce rate of 78.7% and 44.9% unemployment rate among the participants in this study can trigger unhealthy social habits like smoking, drinking and drug abuse. Subscribing to this notion, Pharr et al (2012) posit that unemployment is associated with unhealthy behaviours; and study conducted by Atallah et al (2007) in the Caribbean, indicate that the high prevalence and poor control of hypertension have been observed in populations with low-socioeconomic status including poor therapeutic control in lower social classes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that access to primary care can play a role in the control and management of certain CMRFs [21,[25][26][27][28]. The dimensions of access to primary care can be fundamentally conceptualized into (1) physical access (2) affordability and (3) acceptability [29].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that medical consultations were reported less likely to happen when physical access to health care services is lower [21]. In addition, access to adequate treatment facilities were reported to have an inverse association with certain CMRFs, such as hypertension [25,26], end stage renal disease [27] and diabetes mellitus [32]. However, these reports are based on individual CMRFs but consistent evidence across a range of CMRFs may provide a stronger evidence base for healthcare service commissioning across areas.…”
Section: Introductionmentioning
confidence: 99%
“…On sait la responsabilité de l'HyperTension Artérielle (HTA) dans la survenue d'un AVC. La prévalence de l'HTA aux Antilles françaises n'est pourtant pas très différente de celle observée en France métropolitaine, tout du moins chez les hommes et parmi les actifs ; mais cette prévalence de l'HTA est plus élevée chez les Guadeloupéens privés d'emploi [3].…”
Section: Introductionunclassified